A model of the ocular pharmacokinetics involved in the therapy of neovascular age-related macular degeneration with ranibizumab. Issue 11 (8th May 2015) - Saunders, Derek J; Muether, Philipp S; Fauser, Sascha
Abstract : Background: To develop a model of the pharmacokinetics of vascular endothelial growth factor (VEGF-A) determined in samples of aqueous humour from patients with neovascular age-related macular degeneration (AMD) treated with ranibizumab (Lucentis). Methods: Post hoc analysis of data from 31 eyes of 31 patients with AMD treated with ranibizumab gathered in a non-randomised, prospective clinical study. VEGF-A concentrations were measured in 440 aqueous humour samples by Luminex multiplex bead analysis (Luminex, Austin, Texas, USA). Results: The kinetics of recovery of VEGF-A from suppression by ranibizumab were well described by a simple model: VEGF-A is produced at a constant individual rate; VEGF-A and ranibizumab disperse rapidly within the vitreous chamber and bind with a known affinity; both are eliminated at identical rates from the vitreous chamber in a constant but individual flow into the anterior chamber, and are finally cleared by draining into the peripheral circulation. Average rates of VEGF-A production were predicted to be 5.8 fmol/day (range: 2.7–10.1 fmol), and elimination half-times predicted to be 3.5 days (range: 2.3–5.5 days). The duration of complete VEGF-A suppression in the aqueous humour averaged 41 days (range: 28–67 days). Conclusions: The ocular pharmacokinetics of VEGF-A and ranibizumab have been linked for the first time in a simple and plausible model which suggests that it might be possible to anticipate individual VEGF-A suppression times. Clinical trial number: NCT01213667.